2013
DOI: 10.1084/jem.20121229
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T cells induce proliferation of chronic myeloid leukemia stem cells by secreting interferon-γ

Abstract: Cytotoxic T cells increase leukemia stem cell numbers in a murine model of chronic myeloid leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 76 publications
8
87
0
Order By: Relevance
“…Reduced expression of MICA and MICB by BCSCs contributes to the resistance to NK cell cytotoxicity and the resultant metastasis Tumor-infiltrating immune cells release cytokines such as IFNg to regulate leukemic stem cells (8). However, we found that the expression of IFNg receptor a chain, an essential component of IFNg receptor for ligand binding and trafficking, was comparable between BCSCs and non-BCSCs (Supplementary Fig.…”
Section: Failure Of Tumor-infiltrating Nk Cells To Prevent the Metastmentioning
confidence: 84%
See 3 more Smart Citations
“…Reduced expression of MICA and MICB by BCSCs contributes to the resistance to NK cell cytotoxicity and the resultant metastasis Tumor-infiltrating immune cells release cytokines such as IFNg to regulate leukemic stem cells (8). However, we found that the expression of IFNg receptor a chain, an essential component of IFNg receptor for ligand binding and trafficking, was comparable between BCSCs and non-BCSCs (Supplementary Fig.…”
Section: Failure Of Tumor-infiltrating Nk Cells To Prevent the Metastmentioning
confidence: 84%
“…The potential for CSCs to avoid destruction by adaptive immunity has been documented in the context of CTL-mediated cytotoxicity (5-7, 9, 28). In addition, IFNg released by CTL promotes the proliferation of CSCs and contributes to leukemia progression (8). These observations demonstrate that tumor metastasis is associated with dynamic regulation of CSC evasiveness from adaptive immunity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In analogy Moreover, in leukemia, BM-infiltrating immune cells may contribute to the LSC niche and especially activated T cells interact with and paradoxically support LSCs (12,13,44).…”
Section: Discussionmentioning
confidence: 99%